Strategies for non‐invasive imaging of polymeric biomaterial in vascular tissue engineering and regenerative medicine using ultrasound and photoacoustic techniques. Issue 7 (26th April 2016) - Avigo, Cinzia; Flori, Alessandra; Armanetti, Paolo; Di Lascio, Nicole; Kusmic, Claudia; Jose, Jithin; Losi, Paola; Soldani, Giorgio; Faita, Francesco; Menichetti, Luca
Abstract : Recent advancements of ultrasound and photoacoustic imaging applied to tissue engineering are presented with examples about the assessment of vascular grafts, the microvasculature in absorbable scaffolds and novel nano‐biomaterials applications. Abstract: The ability of new polymeric materials to provide excellent biomechanical properties expanded their potential for biomedical applications enormously. The use of non‐invasive imaging modalities could provide crucial information to monitor the efficacy/effectiveness/efficiency of the new materials employed in 'regenerative' approaches, including scaffolds, hydrogels, self‐assembling materials and nanosized structures. The assessment of the morpho‐functional and metabolic changes of treated or implanted tissues, the visualization of sites of drug delivery and the real‐time check of the in vivo efficacy of therapeutics could be achieved by non‐invasive micro‐ and macro‐imaging techniques. The macro‐ and nano‐requirements of these new materials and their behaviour in vivo can be investigated using standard approaches such as computed tomography, MRI and ultrasound techniques and the emerging photoacoustic imaging. This paper presents recent advancements of ultrasonography and the novel photoacoustic technique to monitor the morpho‐functional parameters of synthetic polymeric scaffolds and conduits in experimental models. © 2016 Society of Chemical Industry